Iron Regulates the Warburg Effect and Ferroptosis in Colorectal Cancer - Yuan, Yin; Ni, Shuo; Zhuge, Aoxiang; Li, Bo; Li, Lanjuan (Frontiers in Oncology, 2021)
Iron promotes the proliferation of cancer cells, but it also contributes to cell death. Here we explored whether iron could promote the Warburg effect of colorectal cancer (CRC) cells and suppress sensitivity to ferroptosis by inducing reactive oxygen species (ROS) and regulating nuclear factor erythroid 2-related factor 2 (NRF2). In this study, cell proliferation abilities were measured by CCK-8, EdU incorporation and colony formation assays. Seahorse XF96 respirometry assays were used to detect the Warburg effect and the level of ROS was assess by DCFH-DA fluorescent probes. Results showed that iron exposure promoted the Warburg effect of CRC cells by inducing ROS and activating NRF2 both in vivo and in vitro. In addition, iron exposure also induced ferroptosis in CRC cells, but at the same time its inhibitory proteins SLC7A11 and GPX4 were also upregulated, indicating an enhanced resistance to ferroptosis. Our results revealed that iron can effectively promote tumorigenesis. Meanwhile, iron elimination or a low-iron diet might be valid therapeutic approaches for CRC.